2006
DOI: 10.1001/archinte.166.1.44
|View full text |Cite
|
Sign up to set email alerts
|

Preemptive Transplantation for Patients With Diabetes-Related Kidney Disease

Abstract: These analyses suggest that PreKT has significant benefits for subsets of patients with types 1 and 2 DM and end-stage renal disease. It also suggests a time trend toward less benefit from preemptive transplants from deceased donors in more recent years compared with the early 1990s. This observation and the discrepancies between RR of graft loss and RR of mortality deserve further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
51
0
8

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 22 publications
(22 reference statements)
1
51
0
8
Order By: Relevance
“…Early studies reported comparable graft and patient survival for preemptive transplant patients and patients transplanted after dialysis (3,4). More recent studies show that preemptive transplantation is associated with better patient and graft survival (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Additional advantages have been documented, such as avoidance of complications with dialysis access infections, reduced severity of sequelae of chronic kidney disease, increased ability to maintain employment, and decreased overall costs (16 -18).…”
supporting
confidence: 85%
“…Early studies reported comparable graft and patient survival for preemptive transplant patients and patients transplanted after dialysis (3,4). More recent studies show that preemptive transplantation is associated with better patient and graft survival (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Additional advantages have been documented, such as avoidance of complications with dialysis access infections, reduced severity of sequelae of chronic kidney disease, increased ability to maintain employment, and decreased overall costs (16 -18).…”
supporting
confidence: 85%
“…Our findings seem to be better than those of other reports. 10,11,29 Because our study group is small, our finding about the effectiveness of pre-emptive kidney transplantation in patients with T1D and ESRD needs to be seen as preliminary. The challenge is how to increase frequency of pre-emptive kidney transplantation in patients with T1D and ESRD.…”
Section: Discussionmentioning
confidence: 97%
“…Among patients with type 1 diabetes, benefits of preemptive transplantation are well defined, but availability of pancreas transplantation may influence the choice of approaches. Indeed, recent data indicate that outcomes with simultaneous kidney-pancreas transplantation from a deceased donor may rival those associated with preemptive transplantation of a kidney alone from a LD (24,25). Finally, although elderly patients make up the fastest growing component of incident patients with ESRD and clearly benefit from preemptive transplantation, an appropriate LD may be less readily identifiable, again necessitating individualization of approaches (26).…”
Section: Preemptive Transplantation and The Ckd Paradigmmentioning
confidence: 99%